2020
DOI: 10.2147/rmhp.s267575
|View full text |Cite
|
Sign up to set email alerts
|

<p>Associations of Physical Activity and Sedentary Time with Metabolic Syndrome in Saudi Adult Males</p>

Abstract: The association between objectively measured sedentary behavior and physical activity with metabolic syndrome (MetS) has been rarely investigated in Saudi Arabia. The purpose of the current study was to examine the association of objectively measured sedentary, light physical activity (LPA), and moderate-vigorous physical activity (MVPA) with MetS among Saudi adult males. Materials and Methods: The study participants were 103 males from Riyadh, Saudi Arabia (mean age = 54.9 ± 10.6 years). Metabolic syndrome wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…In cross-sectional studies, prevalent MetS is directly associated with low cardiorespiratory fitness 99,130 and low levels of PA 131,132 and is inversely associated with “weekend warrior” and regular PA patterns, 133 any length of moderate- to vigorous-intensity PA, 132 and handgrip strength. 134–136…”
Section: Risk Factorsmentioning
confidence: 99%
“…In cross-sectional studies, prevalent MetS is directly associated with low cardiorespiratory fitness 99,130 and low levels of PA 131,132 and is inversely associated with “weekend warrior” and regular PA patterns, 133 any length of moderate- to vigorous-intensity PA, 132 and handgrip strength. 134–136…”
Section: Risk Factorsmentioning
confidence: 99%
“…Four prospective cohort studies 28–31 and six cross‐sectional studies 32–34,36,37,40 with a total of 31,106 adults (13,105 men and 18,001 women) reported the categorical association between total sedentary time and the risk of MetS independent of physical activity (Table 2; Figures S1–S4). Compared with those in the lowest category, adults in the highest (median duration: 7.26 h/day, interquartile range: 6.00–8.13 h/day) and intermediate (median duration: 4.11 h/day, interquartile range: 3.91–4.77 h/day) categories of total sedentary time were significantly associated with an increased risk of MetS.…”
Section: Resultsmentioning
confidence: 99%
“…After the title and abstract screening and full-text review, 24 eligible studies were included, and another two studies were added through a manual search of the reference lists. Inclusion criteria were totally met in 26 studies, including four prospective cohort studies [28][29][30][31] and 22 cross-sectional studies 7,32-52 with 105,239 unique participants (39,369 children and adolescents 7,42,49,50 and 65,870 adults [28][29][30][31][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48]51,52 ) and 16,185 MetS cases (1,081 children and adolescents and 15,104 adults). The follow-up periods ranged from 9.6 ± 6.9 years to 1 year.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations